Çok partili sisteme geçiş sürecinde CHP’de ideolojik arayışlar: (1945-1950) - Demirci, Emine (My University, 2007)
Ülkelerin tarihlerinde bazı dönemler o ülkenin geleceği için büyük önem taşımaktadır. Türkiye tarihi söz konusu olduğunda ise Cumhuriyet Halk Partisinden ayrı bir tarih düşünülemez. Cumhuriyet Halk Partisi yirmi yedi yıllık iktidarı döneminde tek parti olarak ülkenin kaderini derinden etkilemiştir. 1923-1950 yılları arasındaki yapılan çalışmalara da bu yönüyle ışık tutmuştur. Mustafa Kemal Atatürk tarafından kurulan parti devrimleri koyan ve uygulayan parti olarak bu devrimlerle özdeşleşmiş ve kendini bu devrimlerin koruyucusu görmüştür. Tek parti iktidarına rağmen çok partili siyasi hayata geçiş denemelerinde de bulunmuştur. Bu denemeler parti için tecrübe oluşturmuş ve zaman zaman da politikasında değişmelere arayışlara sebep olmuştur.Özellikle II.Dünya Savaşı ve sonrasında Demokrat Parti’nin de kurulmasıyla Cumhuriyet Halk Partisi’nin politikasında iktidarını sağlamlaştırmak ve kaybetmemek adına ılımlı politika izlediği gözlenmektedir.

Some periods within the histories of countries carry significant importance for the future of them. When it comes to Turkey’s history, Republican People’s Party cannot be separated from her history. Being the only party in Turkey, Republican People’s Party has deeply affected the country’s destiny for twenty-seven years during which they have been in power. Thus, it has enlightened the studies done between the years 1923-1950. Having been founded by Mustafa Kemal Atatürk, Republican People’s Party, which has put forth revolutions and implemented them, have identified itself with them and seen itself as the guard of them. There have been many attempts for transition to multi-party political period inspite of one-party-in-power period. These attempts have been lessons-to-be-drawn for the party and caused the party to look for modifications in its policies occasionally. Especially after World War II and establishment of Democrat Party, it’s been observed that Republican People’s Party has changed to a moderate view in order to reinforce and maintain its power in the country.
Keywords: Cumhuriyet Tarihi; Siyaset ve Yönetim